1997
DOI: 10.1016/s0014-5793(97)00761-8
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human glycosylasparaginase catalyzes hydrolysis of l‐asparagine

Abstract: Glycosylasparaginase is a lysosomal amidase involved in the degradation of glycoproteins. Recombinant human glycosylasparaginase is capable of catalyzing the hydrolysis of the amino acid L-asparagine to L-aspartic acid and ammonia. For the hydrolysis of L-asparagine the K m is 3-4-fold higher and V-mnx 1/5 of that for glycoasparagines suggesting that the full catalytic potential of glycosylasparaginase is not used in the hydrolysis of the free amino acid. L-Asparagine competitively inhibits the hydrolysis of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…3 Glycosylasparaginase is transported in active form into various non-neuronal cell types, including Epstein-Barr virus-transformed (EBV) glycosylasparaginase-deficient lymphoblasts, and it effectively corrects the metabolic defects in glycosylasparaginase-deficient cell lines 4 and mice. 5 The finding that human glycosylasparaginase also hydrolyzes L-asparagine to L-aspartic acid and ammonia-like bacterial L-asparaginases 6 without any L-glutaminase activity 3 led us to investigate its potential cytotoxic activity toward leukemia cells that are dependent on their external supply of L-asparagine.…”
Section: Depletion Of L-asparagine Supply and Apoptosis Of Leukemia Cmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Glycosylasparaginase is transported in active form into various non-neuronal cell types, including Epstein-Barr virus-transformed (EBV) glycosylasparaginase-deficient lymphoblasts, and it effectively corrects the metabolic defects in glycosylasparaginase-deficient cell lines 4 and mice. 5 The finding that human glycosylasparaginase also hydrolyzes L-asparagine to L-aspartic acid and ammonia-like bacterial L-asparaginases 6 without any L-glutaminase activity 3 led us to investigate its potential cytotoxic activity toward leukemia cells that are dependent on their external supply of L-asparagine.…”
Section: Depletion Of L-asparagine Supply and Apoptosis Of Leukemia Cmentioning
confidence: 99%
“…The pelleted cells were washed twice with ice-cold phosphate-buffered saline (PBS) and then lysed in 50 mM sodium-potassium phosphate buffer, pH 7.5, through three freezing-thawing cycles and sonication in an ice bath for 30 s. The enzyme activity was measured by a fluorometric assay 4 and the Asn concentration was analyzed with high-performance liquid chromatography. 6 Letters to the Editor GA or two bacterial L-asparaginases used in chemotherapy, Erwinase s (ErAII) and Elspar s (E. coli L-asparaginase, EcAII). The sensitivity of the cells to each enzyme was tested with the MTT assay.…”
Section: Depletion Of L-asparagine Supply and Apoptosis Of Leukemia Cmentioning
confidence: 99%
“…2. We propose the name glycosylasparaginase/␤-aspartyltransferase for the multifunctional enzyme that catalyzes the enzymatic synthesis and degradation of ␤-aspartyl peptides, cleaves the Nglycosidic bond during degradation of glycoproteins (26), and possesses L-asparaginase activity (12). Because GGT is also an Ntn hydrolase (7) and there are many biochemical similarities between GGT and GA, we predict that the binding mode of the nucleophile amino acids and peptides into the active site of GGT resembles the nucleophile binding to GA.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme uses the ␥-hydroxyl and ␣-amino group of its ␤-chain N-terminal threonine as an active site nucleophile and general base in the formation of ␤-aspartyl enzyme, which is subsequently deacylated by water to L-aspartic acid (10,11). The GA-catalyzed hydrolysis of L-asparagine occurs in a similar manner, resulting in the formation of ␤-aspartyl enzyme and ammonia (12).…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that mammalian tissues contain a lysosomal enzyme, glycosylasparagi-nase (glycoasparaginase, aspartylglucosaminidase; EC 3.5.1.26), which can catalyze the hydrolysis of L-asparagine to L-aspartic acid and ammonia (8). Glycosylasparaginase has a mechanism of action similar to that of L-asparaginase (9 -11) and its activity can be assayed fluorometrically using L-aspartic acid ␤-(7-amido-4-methylcoumarin) (AspAMC) as substrate (12).…”
mentioning
confidence: 99%